2008
DOI: 10.1002/dvg.20453
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial‐mesenchymal crosstalk in Wolffian duct and fetal testis cord development

Abstract: SummaryInteractions between adjacent epithelial and mesenchymal tissues represent a highly conserved mechanism in embryonic organogenesis. In particular, the ability of the mesenchyme to instruct cellular differentiation of the epithelium is a fundamental requirement for the morphogenesis of tubular structures such as those found in the kidneys, lungs, and the developing male reproductive system. Once the tubular structure has formed, it receives signals from the mesenchyme, which can control proliferation, pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 74 publications
0
12
0
Order By: Relevance
“…Communication between the epithelium and mesenchyme is a two-way street. Interplay between the stromal and epithelial compartments of the developing reproductive tract is essential for normal epididymal development (Atanassova et al 2005;Archambeault et al 2009).…”
Section: Theory Regarding the Origin Of Basal Cellsmentioning
confidence: 99%
“…Communication between the epithelium and mesenchyme is a two-way street. Interplay between the stromal and epithelial compartments of the developing reproductive tract is essential for normal epididymal development (Atanassova et al 2005;Archambeault et al 2009).…”
Section: Theory Regarding the Origin Of Basal Cellsmentioning
confidence: 99%
“…We and others have also shown that CA β-catenin causes sterility in males by inhibiting postnatal Sertoli maturation and spermatogenesis (18)(19)(20). Given the requirement for Wnt signaling in MD development (21) and the relative paucity of reports linking Wnt signaling and Wolffian duct (WD) differentiation, we examined whether dysregulated β-catenin activity in the adjacent MD mesenchyme affected normal WD development into the epididymis, vas deferens, and seminal vesicles (22,23). We show that CA β-catenin expression in the MD mesenchyme results in focal MD retention and adjacent WD obstruction, which leads to azoospermia and infertility secondary to seminiferous tubule degeneration and defective spermatogenesis that develops later in the adult (18,19).…”
mentioning
confidence: 99%
“…Wolffian duct differentiation into the epididymides, vas deferentia, and seminal vesicles starts at E15.5 and is completed within the first 2 weeks of postnatal life (Archambeault et al, 2009). In contrast, primordial follicles, the first stage of ovarian folliculogenesis, form between P1 and P3 (Wilhelm et al, 2007), and Müllerian ducts differentiate into the oviducts, uterus, cervix, and upper vagina during the first 2 weeks of postnatal life.…”
Section: Resultsmentioning
confidence: 99%